A Meta‐Analysis of Logistics Customer Service. Issue 1 (22nd January 2013) - Leuschner, Rudolf; Charvet, François; Rogers, Dale S.
<x xml:space="preserve">Abstract</x> Logistics customer service has received considerable attention over the past several decades. Evidence exists that superior logistics customer service leads to better overall firm performance. Yet mixed findings were observed, and this relationship has been tested across multiple operationalizations and diverse industry settings, which may contribute to these mixed findings. There is thus a need for a systematic analysis that examines all of the prior evidence in an aggregate inquiry of logistics customer service. Meta‐analysis, which is a relatively under‐utilized methodology in supply chain management research, is applied to provide a quantitative examination of 37 sample studies and an assessment of overall population effects. The main contribution of this research is that we statistically aggregate and summarize existing research on logistics customer service. In addition, moderators that affect the relationship between logistics customer service and firm performance are examined. The results provide evidence that logistics customer service has a significant positive relationship with firm performance; however, significant heterogeneity was detected. This points to areas in need of additional research in order to obtain generalizable evidence.